Knowledge, Attitude and Practice of the Nephrotoxic Effects of Skin Bleaching Among Women in Akure Metropolis - Olafusi, Oluwatosin S.; Adeyeye, Ayomide B. (American Journal of Biomedicine and Pharmacy, 2025)
Background: Skin bleaching (SB) is a practice that keeps rising among Nigerian women. The prevalence is as high as 77.3%, making Nigeria the leading country in Africa. It is associated with various adverse effects on the kidney health especially when agents containing ingredients such as mercury and steroids are used. It is therefore important to eliminate the practice of skin bleaching to reduce the associated nephrotoxic effects. Objective: The aim of this study is to evaluate the knowledge, attitude and practice of skin bleaching and its nephrotoxic effect among women in Akure metropolis, Ondo State, Nigeria. Method: This was a cross-sectional descriptive study among 269 women in Akure. They were interviewed using a self-administered questionnaire. The questionnaire sought information on the knowledge, attitude and practice of skin bleaching. Data was analyzed using IBM SPSS. Result: A total of 269 women with a mean age of 29.16 ± 9.60 years completed the survey Most (65.7%) of the respondents had a good knowledge of skin bleaching. A majority (93.2%) had heard about skin bleaching, while 55.3% knew that skin bleaching can affect kidney health. Among the study participants, 140 (53.0%) were using skin bleaching products. Level of education, marital status and occupation were significantly associated with skin bleaching (p<0.05) Conclusion: The level of knowledge and attitudes towards the effects of skin bleaching on kidney health were found to be good. However, the practice was found to be high in more than half of the respondents. Therefore, regulation and control skin bleaching products’ sales and use should be implemented.